2019
DOI: 10.3389/fbioe.2019.00177
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production and Molecular Weight of Artificial Polyhydroxyalkanoate Poly(2-hydroxybutyrate) Above the Glass Transition Temperature Threshold

Abstract: Poly(2-hydroxybutyrate) [P(2HB)] is an artificial polyhydroxyalkanoate (PHA) synthesized using engineered 2-hydroxyalkanoate-polymerizing PHA synthase. In the present study, the effect of temperature on P(2HB) synthesis was investigated. Recombinant Escherichia coli harboring PHA synthetic genes were cultivated with 2HB and 3-hydroxybutyrate (3HB) supplementation at varied temperatures ranging from 24 to 36°C for the synthesis of P(2HB) and natural PHA P(3HB), respectively. P(2HB) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
(35 reference statements)
1
12
0
1
Order By: Relevance
“…The T g of the polymer product also influences polymer synthesis. Our recent study revealed that P(2HB) biosynthesis is efficient when the cultivation temperature is higher than the T g of the polymer ( Matsumoto and Kageyama, 2019 ). Given the fact that the random copolymer possesses a lower T g than that of polyglycolate (35–40°C), P(GL- ran -3HB) chains are more readily synthesized than the homopolymer.…”
Section: Discussionmentioning
confidence: 99%
“…The T g of the polymer product also influences polymer synthesis. Our recent study revealed that P(2HB) biosynthesis is efficient when the cultivation temperature is higher than the T g of the polymer ( Matsumoto and Kageyama, 2019 ). Given the fact that the random copolymer possesses a lower T g than that of polyglycolate (35–40°C), P(GL- ran -3HB) chains are more readily synthesized than the homopolymer.…”
Section: Discussionmentioning
confidence: 99%
“…The polymerization and molecular weight are affected by C:N ratio [39] and are governed by the specificity of the substrate of PHA synthase [36]. The reaction temperature [36] is another vital component contributing to its polymerization and high molecular weight. Nutrient limiting media one of the essential factors contributing to PHA granule formation.…”
Section: Structural Diversity Of Phamentioning
confidence: 99%
“…The polymerization of the monomeric components of the PHA nano-sized granule depends on the activity of PHA synthase [ 36 ] This helps to achieve the desired high molecular weight of the resultant PHA homopolymer and copolymers. The gel permeation chromatography results showed that in marine bacteria, the number average molecular weight of the PHAs after purification ranged from 3 × 10 3 –9.94 × 10 5 g/mol [ 37 ].…”
Section: Structural Diversity Of Phamentioning
confidence: 99%
See 2 more Smart Citations